Does Tax Amnesty Reduce Tax Risk in Indonesia? - Firmansyah, Amrie; Kartiko, Nafis Dwi (Journal of Accounting Research, Organization and Economics, 2023)
Objective This study examines tax risk before and after the implementation period of the tax amnesty policy in Indonesian listed companies.Design/methodology The method employed in this study is a quantitative approach. The research data is in the form of information in financial statements obtained from www.idx.co.id for 2011-2015 and 2017-2021. The population used in this study is all companies listed on the Indonesian Stock Exchange from 2011 to 2021. This study obtains 182 observations based on the purposive sampling method. Hypotheses were tested using the Wilcoxon Signed Rank Test.Results This research concludes that there is a tax risk reduction following the tax amnesty implementation based on cash ETR and GAAP ETR. These results indicate that the ratio of cash tax to pre-tax income paid by companies after the tax amnesty policy experienced a significant reduction in volatility, as well as the comparison of corporate income tax to pre-tax income after the implementation of the tax amnesty policy.Research Limitations/Implications Several sampling criteria, such as excluding GAAP ETR and Cash ETR values that are negative and greater than 1, result in a reduced sample size. In addition, this study only uses data from listed companies to facilitate access to the data used in the study.Novelty/Originality Previous studies have focused on the causality between tax risk, firm risk, or other predictive variables. This study tests tax risk before and after implementing the tax amnesty policy. Thus, this study can capture the significance of changes in the volatility of taxpayers' tax payments/ expenditures before and after the implementation of the tax amnesty in Indonesia.